The Relationship Between Food Waste Management and Fly Density Level at Padang Restaurants in Tembalang District, Semarang City - Paramitha, Sekar Sandya; Sulistiyani, Sulistiyani; Dewanti, Nikie Astorina Yunita; Suhartono, Suhartono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Padang restaurants have become one of the favorite places for residents of Tembalang District because of the distinctive taste of the food they serve. However, many Padang restaurants have not managed their waste properly. This study aimed to determine the relationship between waste management and fly density levels at Padang restaurants in the Tembalang District. This was an analytical study with a cross-sectional design. The study was conducted from October to December 2023. The research sample consisted of 45 Padang restaurants selected using total sampling technique. The results show that most food waste comes from customer plate waste (60%) with rice being the most wasted food type (37.8%). The majority of restaurants have a relatively poor waste sorting category (68.9%) but mostly the waste containers meets the requirements (75.6%). Fly density levels in Padang restaurants mostly are still categorized as high (53.5%). Waste containers is associated with fly density levels (p=0.030), while waste sorting is not associated with fly density levels (p=0.057). It could be concluded that waste containers without lids with insufficient capacity are associated with fly density levels at Padang restaurants in Tembalang District.